Simulasi Model Servqual Untuk Layanan Pengunjung Perpustakan AMIK XYZ - Sugeng Murdowo (Jurnal Kajian Ilmiah, 2024)
This research aims to find out the extent of satisfaction of visitors to the AMIK XYZ library after visiting and using the facilities in the library. So far, the AMIK XYZ library has never conducted a customer satisfaction survey regarding library services. To simulate measuring customer satisfaction, library customer service uses the Servqual Method, one of the methods used to measure customer service service gaps. The results of the simulation for measuring customer satisfaction using the SERVQUAL method, using a sample of ten respondents and only one dimension was measured, namely the Responsiveness dimension (responsiveness). Simulation results of calculations of Service Gap Responsiveness (-1.5), Providing fast service to users (-1.9), Willingness to help users (-2), Paying attention to users when informing about services (-1.6), Readiness to answer user questions (-1.9) The measurement results show that the service gap in the Responsiveness dimension is still far from the expectations of AMIK XYZ library visitors, so it must be improved by the AMIK XYZ library manager.